The effect of 6-stage evaluation questions and supportive activities applied at the end of drama plays on learning emotion concepts in 60-72 month-old children - (:unkn) unknown (Sakarya University, 2015)
The purpose of this study is to prove the effect of 6-stage evaluation questions and supportive activities applied at the end of drama plays on learning emotion concepts by 60-72 month-old children. The study group was divided to three with 14 children in Experimental1, 13 children in Experimental2 and 14 children in control groups. The data collection tool used in the study was Emotion Concepts subscale of Concept Development Scale. A program was developed by the researchers to teach emotion concepts of happy, sad, angry, confused, and afraid. The program was applied as activities of 45-minute duration once a week for 8 weeks. Results of the study demonstrated that applying evaluation and supportive activities through 6-stage evaluation/discussion questions and supportive activities as suggested by Önder (1995) following drama plays ensures emotion concepts are learned in the ultimate way compared to other approaches (using drama only or not applying drama at all). © The Turkish Online Journal of Educational Technology.